Case report: Right ventricular outflow tract obstruction caused by multicomponent mesenchymal tumor - Huang, Shengyuan; Wang, Shiye; Tang, Zhixiang; Dai, Yinghuan; Song, Long (Frontiers in Cardiovascular Medicine, 2022)
Right ventricular outflow tract obstruction (RVOTO) is a cause of hemodynamic instability that can lead to right ventricular dysfunction. Cardiac tumors located in the right ventricle or surrounding structures can cause RVOTO. Herein, we present a rare case of a 21-year-old male with palpitations due to RVOTO caused by a cardiac multicomponent mesenchymal tumor. The tumor was localized in the right ventricular outflow tract, resulting in right side heart enlargement, tricuspid regurgitation, and RVOTO. Hence, tumor resection was performed. The patient was in a stable condition and discharged home on the 6th post-operative day. However, histopathological examination of the tumor specimen suggested a three-component mesenchymal tumor containing mucinous components, formed blood vessels, and fibrous tissue, which is like an atypical capillary hemangioma. After seven years of follow-up, the patient had no right heart enlargement, tricuspid regurgitation, and tumor recurrence. We believe surgical treatment is effective, and this case will provide a reference for clinicians to treat and evaluate the prognosis of similar three-component mesenchymal cardiac tumor cases in the future.